The Impact of Website Interactivity in Crowdfunding Platform - Wan Nur Fazni Wan Mohamad Nazarie; Hanim Hj Misbah; Junaidah Abu Seman; Nur Ainna Ramli; Aulia Rahman Zulkarnain; Hafiza Abdul Hamid (Universiti Sains Islam Malaysia, 2024)
Page : 141-144